Dopamine Homeostasis Imbalance and Dopamine Receptors-Mediated AC/cAMP/PKA Pathway Activation are Involved in Aconitine-Induced Neurological Impairment in Zebrafish and SH-SY5Y Cells - Zhou, Jie; Peng, Cheng; Li, Qiuju; Yan, Xiaoyu; Yang, Liang; Li, Mengting; Cao, Xiaoyu; Xie, Xiaofang; Chen, Dayi; Rao, Chaolong; Huang, Sizhou; Peng, Fu; et al. (Frontiers in Pharmacology, 2022)
Aconitine is one of the main bioactive and toxic ingredients of Aconitum species. Increasingly, aconitine has been reported to induce neurotoxicity. However, whether aconitine has effects on dopaminergic nervous system remains unclear. In this study, zebrafish embryos at 6 day postfertilization were exposed to aconitine at 0.5, 1, and 2 μM for 24 h, and SH-SY5Y cells were treated with 50, 100, and 200 μM aconitine for 24 h. Results demonstrated that aconitine treatment induced deformities and enhanced swimming behavior of zebrafish larvaes. Aconitine exposure suppressed cell proliferation, increased the number of reactive oxygen species (ROS) and apoptosis both in zebrafish larvaes and SH-SY5Y cells. Aconitine altered the levels of dopamine and its metabolites by altering the expression of genes and proteins related to dopamine synthesis, storage, degradation, and reuptake in vivo and in vitro. Moreover, aconitine activated the AC/cAMP/PKA pathway by activating dopamine D1 receptor (D1R) and inhibiting dopamine D2 receptor (D2R) to disturb intracellular calcium homeostasis and eventually lead to the damage of nerve cells. Furthermore, the D1R antagonist SCH23390 and D2R agonist sumanirole pretreatment effectively attenuated the excitatory state of larvaes and intracellular Ca(2+) accumulation induced by aconitine through inhibiting the AC/cAMP/PKA pathway in vivo. SCH23390 and sumanirole also reduced aconitine-induced cytotoxicity through inhibiting the AC/cAMP/PKA pathway in vitro. These results suggests that dopamine homeostasis imbalance and dopamine receptor (DR)-mediated AC/cAMP/PKA pathway activation may be vital mechanisms underlying aconitine-induced neurological injury.